PERLINDUNGAN HUKUM TERHADAP PEMEGANG HAK PATEN SEDERHANA YANG TERDAFTAR LEBIH DAHULU DI DIREKTORAT PATEN (STUDI PUTUSAN MAHKAMAH AGUNG NO. 437K/PDT.SUS-HK/2018 - Rahmad Anwar Lubis (Journal Law of Deli Sumatera, 2021)
Patents are exclusive rights granted by the state to inventors for their inventions in the field of technology, for a certain period of time. A simple patent is an exclusive right granted by the Patent Directorate Office to a patent holder to realize a new invention, either in the form of a product or a certain process. If a simple patent does not contain an element of novelty or does not contain an element of progress, a simple patent may be rejected for registration at the Directorate. The type of research used in this research is normative legal research. The nature of this research is descriptive analytical where this research seeks to describe, describe and analyze the problems that arise, then look for the correct answer as a solution to the problem. The results of the discussion of the problems that arise in this research, the rights to simple patents contain elements of novelty or are the development of a technology from simple patent products from existing simple patent products. The simple patent holder must be protected by law if another party sues the registered simple patent product The panel of judges of the Supreme Court in their legal considerations have complied with the provisions of the legislation in the field of patents in this case is Law No. 13 of 2016 concerning Patents, where the judge's legal consideration is that the plaintiff / respondent for cassation YA does not have a strong juridical basis in filing a lawsuit for cancellation simple patent